ANALISIS PENGARUH VARIABEL FUNDAMENTAL DAN VARIABEL MAKRO (UNCONTROLABLE) TERHADAP HARGA SAHAM (Study Empiris pada Perusahaan Industri Property yang go-publik di BEI ) - Mawardi, M. Cholid (Fakultas Ekonomi, UIN Maliki Malang, 2009)
This research is employed 35 property companies that was listed at BEI. The research objective is testing the influance of fundamental variable and macro variable (uncontrolable) towards stock price. Fundamental variables consist of equity to net profit (X1), liquidity ratio (X2), quick ratio (X3), cash ratio (X4), debt equity ratio (X5), price earning ratio (X6), book market value (X7), and earning per share (X8). Macro variables consist of inflation (X9), deposit rate (X10), and economic growth / sale (X11). The result shows all of variables are significantly influance simultaneously towards stock price which indicated by F test = 5.567 on significant level = 0.000. Partially, 6 variables are significantly influance towards stock price there are : X1 (sig level = 0.021; t test = 2.368), X2 (sig level = 0.039; t test = 2.141), X6 (sig level = 0.017; t test = 2.413), X7 (sig level = 0.000; t test = 5.383), X8 (sig level = 0.039; t test = 2.173), X10 (sig level = 0.047; t test = -1.921). Inflation variable is the dominant variable with coeffisien value -1019.402.